Mekanisme Pembiayaan Mitra Guna Berkah Pns Dengan Akad Murabahah Pada Bank BSI KCP Panyabungan - Nasution, Wahyudi (JPSDa: Jurnal Perbankan Syariah Darussalam, 2024)
This research aims to determine the partner financing mechanism for blessings for civil servants with murabahah contracts at Bank Syariah Indonesia (BSI) KCP Panyabungan, to find out the obstacles in the partner financing mechanism for blessings. Financing is one of the sharia banking services where the budget is circulated to other parties. Financing carried out by banks can work together to fulfill the wishes of the community. The distribution of the budget in the form of financing is based on the trust submitted by the budget owner to the budget consumer. One of the consumers is Civil Servants (PNS). This type of research uses qualitative. The research object studied was the partner financing mechanism for civil servant blessings carried out at Bank Syariah Indonesia KCP Panyabungan. The results show that there are three stages of the mutra financing mechanism for blessings for civil servants at Bank Syariah Indonesia KCP Panyabungan who use a murabahah contract during the disbursement process.